Studi Fenomenologis tentang Kecemasan Akademik Mahasiswa Tingkat Akhir STIT Al-Khairiyah Cilegon - Hartono, Rudi; Kurnaesih, Uun (LPPM STAI La Tansa Mashiro, 2025)
This study aims to reveal and understand in depth the experience of academic anxiety experienced by final year students of STIT Al-Khairiyah Cilegon in the process of preparing a thesis. The approach used is qualitative with phenomenological method, which allows researchers to explore the subjective meaning of anxiety felt by participants. Data was collected through in-depth interviews with several final year students who were preparing their final project. The results showed that academic anxiety appears in various forms, including emotional anxiety (such as fear, anxiety, and hopelessness), cognitive (difficulty concentrating and over thinking), and physical (sleep disturbance and fatigue). The main triggering factors include family pressure, uncertainty about the future, obstacles in the guidance process, and lack of self-confidence. Nevertheless, students developed various coping strategies such as getting closer to Allah SWT, seeking social support, and managing time better. This study recommends the importance of the role of educational institutions in providing academic and psychological assistance services to help students manage their anxiety constructively.